Factors Affecting Finance Administration Efficiency of the Hospital - จังพานิช, วาสนา (Hua Hin Medical Journal, 2019)
This research aims to study the level of administrative factors, the financial administration efficiency and the administrative factors affecting financial administration of the hospital. The study population contains 43 people involved all men and women who work in financial management of Hua Hin Hospital for 6 months. A questionnaire with reliability of administrative factors was .979 and the fiscal management efficiency was .956. The methods used in statistical data analysis were frequency, percentage, mean, standard deviation and multiple regression analysis. The research found that 1. The level of administrative factors was found to be at a high level. 2. The financial administration efficiency of the hospital was found at a high level. 3. There are 3 administrative factors affecting the financial administration of the hospital: of the hospital are 3 factors: Personnel knowledge, management method, and organizational strategy. All independent variables showed the variance of 87.4 percent as statistically significant at the .05. The results of this research indicate that organizations should provide personnel with skills training and skills development that are relevant to the financial and fiscal performance. In the case of executives, they will need to support and encourage the personnel in this field to have the knowledge and regulation in the work. And for the corporate strategy, it must be clear. Leading to action this will make the overall of fiscal management efficiency clearer.